Redesign of the DAB converter with considerations of its stability issue - Zhang, Shuying (2019)
Modularization and unitization of electrical power conversion devices have become new development trends. The dual active bridge (DAB) converter is a typical sub-module, which is widely applied in distributed power supply to provide the required power interface form for smart interconnected grid. However, there are still many problems to be solved in actual use. When the DAB converter operates individually, the control method may influence the stability. Furthermore, another key issue is due to the existence of the impedance interaction, the cascaded converter systems often suffer instability, although the DAB converters have been designed separately for stable operation previously. Therefore, the aim of the project is to study the stability issue of DAB converter. Focusing on the DAB converter controlled by single phase-shift mode, firstly, the minor loop gain T is obtained from the matrix forms of some significant variables in DAB converter by using the MATLAB, and lately, the Nyquist plots of T is analyzed to judge if the system is stable. And then by modeling the PID converter, the parameters design guideline is set. Finally, the stability analysis is verified by the simulation results. In addition, in order to address the stability problem of the DAB converter cascaded system, the impedance model is utilized. The input impedance of the load system should always exceed the peak output impedance of the source converter, which is required by the Middlebrook’s impedance criterion. And concurrently the resonant parameters are determined to proceed the simulation. Eventually, the impedance model and stability analysis are demonstrated by the simulation results.